Analisis Bea Pengalihan Hak atas Tanah dan Bangunan (BPHTB) dan Diskon Penjualan pada Perusahaan Developer guna Menentukan Harga Jual (Studi Kasus pada PT. Agung Saridewi Mandiri) - Septantri, Cornelia Gita; Srikalimah, Srikalimah; Selviasari, Rike (Jurnal Ilmiah Cendekia Akuntansi; Vol 8 No 2 (2023): April, 2023)
This research aims to analyze the Acquisition of Rights to Land and Buildings Tax (BPHTB) and sales discounts on the determination of selling prices at PT Agung Saridewi Mandiri with its housing project, Kediri Family Residence. BPHTB is one type of tax that must be paid when buying a house, 5% of the purchase price minus the Tax-Free Tax Object Sales Value. PT Agung Saridewi Mandiri has faced several buyers who are constrained by BPHTB costs. The  company needs to make appropriate sales discount calculations, so that it can be a target chosen by buyers and still get the appropriate profit. This research is a quantitative descriptive research. The variables in this research are the BPHTB as the independent variable X1, sales discounts as the independent variable X2, and determination of selling price as the dependent variable Y. The results of this research indicate that the amount of discount given by the company during 2020 to 2021, if the company applies a 15% discount on its products as a whole, is Rp 2.070.750.000. This makes the price of the company's product Rp 11.734.250.000, and the selling price of the company's product, taking into account discounts and BPHTB, is Rp 12.284.962.500.